Retinoic acid worsens ATG10-dependent autophagy impairment in TBK1-mutant hiPSC-derived motoneurons through SQSTM1/p62 accumulation - Catanese, Alberto; Heuvel, Florian Olde; Mulaw, Medhanie; Demestre, Maria; Higelin, Julia; Barbi, Gotthold; Freischmidt, Axel; Weishaupt, Jochen H.; Ludolph, Albert C.; Roselli, Francesco; Böckers, Tobias M. (Autophagy, 2019)
Mutations in the TBK1 (TANK binding kinase 1) gene are causally linked to amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). TBK1 phosphorylates the cargo receptors OPTN and SQSTM1 regulating a critical step in macroautophagy/autophagy. Disruption of the autophagic flux leads to accumulation of cytosolic protein aggregates, which are a hallmark of ALS. hiPSC-derived TBK1-mutant motoneurons (MNs) showed reduced TBK1 levels and accumulation of cytosolic SQSTM1-positive aggresomes. By screening a library of nuclear-receptor-agonists for modifiers of the SQSTM1 aggregates, we identified 4-hydroxy(phenyl)retinamide (4HPR) as a potent modifier exerting detrimental effects on mutant-TBK1 motoneurons fitness exacerbating the autophagy overload. We have shown by TEM that TBK1-mutant motoneurons accumulate immature phagophores due a failure in the elongation phase, and 4HPR further worsens the burden of dysfunctional phagophores. 4HPR-increased toxicity was associated with the upregulation of SQSTM1 in a context of strongly reduced ATG10, while rescue of ATG10 levels abolished 4HPR toxicity. Finally, we showed that 4HPR leads to a downregulation of ATG10 and to an accumulation of SQSTM1+ aggresomes also in hiPSC-derived C9orf72-mutant motoneurons. Our data show that cultured human motoneurons harboring mutations in TBK1 gene display typical ALS features, like decreased viability and accumulation of cytosolic SQSTM1-positive aggresomes. The retinoid 4HPR appears a strong negative modifier of the fitness of TBK1 and C9orf72-mutant MNs, through a pathway converging on the mismatch of initiated autophagy and ATG10 levels. Thus, autophagy induction appears not to be a therapeutic strategy for ALS unless the specific underlying pathway alterations are properly addressed.Abbreviations 4HPR: 4-hydroxy(phenyl)retinamide; AKT: AKT1 serine/threonine kinase 1; ALS: amyotrophic lateral sclerosis; ATG: autophagy related; AVs: autophagic vesicle; C9orf72: chromosome 9 open reading frame 72; CASP3: caspase 3; CHAT: choline O-acetyltransferase; CYCS: cytochrome c, somatic; DIV: day in vitro; FTD: frontotemporal dementia; FUS: FUS RNA binding protein; GFP: green fluorescent protein; hiPSCs: human induced pluripotent stem cells; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MNs: motoneurons; mRFP: monomeric red fluorescent protein; MTOR: mechanistic target of rapamycin kinase; NFE2L2/NRF2: nuclear factor, erythroid 2 like 2; RARA: retinoic acid receptor alpha; SLC18A3/VACHT: solute carrier family 18 (vesicular acetylcholine transporter), member 3; SQSTM1/p62: sequestosome 1; TBK1: TANK binding kinase 1; TEM: transmission electron microscopy
Gesehen am 16.06.2021